A Risk Assessment Model for Banks - Tsomocos, D; Goodhart, C; Sunirand, P (2005)
The objective of this paper is to propose a model to assess risk for banks. Its main innovation is to incorporate endogenous interaction between banks, recognising that the actual risk to which an individual bank is exposed also depends on its interaction with other banks and other private sector agents. To this end, we develop a two-period general equilibrium model with three active heterogeneous banks, incomplete markets, and endogenous default. The setting of three heterogeneous banks allows us to study not only interaction between any two individual banks, but also their interaction with the rest of the banks in the banking system. We show that the model is analytically tractable and can be calibrated against real UK banking data and therefore can be implemented as a risk assessment tool for financial regulators and central banks. We address the impact of monetary and regulatory policy as well as credit and capital shocks in the real and financial sectors.